1979
DOI: 10.1002/ajh.2830070404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc on hyperammonemia in sickle cell anemia subjects

Abstract: An increase in plasma ammonia level in human volunteers on restricted zinc intake, and in zinc-deficient rats, has recently been reported. Inasmuch as zinc deficiency has been observed in sickle cell anemia patients, we measured plasma ammonia levels in such subjects. In this report we document hyperammonemia in sickle cell anemia patients that was corrected with zinc therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Zinc deficiency is relatively common in adults with SCD, affecting about 60%-70% of adult subjects in our center [23][24][25]. In SCD patients, our diagnosis of zinc deficiency is based on zinc levels in lymphocytes and granulocytes [12,20,[23][24][25].…”
Section: Studies In Persons With Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc deficiency is relatively common in adults with SCD, affecting about 60%-70% of adult subjects in our center [23][24][25]. In SCD patients, our diagnosis of zinc deficiency is based on zinc levels in lymphocytes and granulocytes [12,20,[23][24][25].…”
Section: Studies In Persons With Scdmentioning
confidence: 99%
“…In SCD patients, our diagnosis of zinc deficiency is based on zinc levels in lymphocytes and granulocytes [12,20,[23][24][25]. Increased hemolysis in SCD patients releases a considerable amount of zinc, which circulates in the plasma pool.…”
Section: Studies In Persons With Scdmentioning
confidence: 99%
“…We have previously shown that growth delays, hypogonadism in males, abnormal dark adaptation and hyperammonemia in SCD patients were related to zinc deficiency and corrected by zinc supplementation [24,[32][33][34]. I will now summarize our studies related to immune functions in SCD.…”
Section: Studies In Patients With Sickle Cell Disease (Scd)mentioning
confidence: 93%
“…Zinc deficiency is common in adult sickle cell disease (SCD) patients, affecting approximately 60-70% of adult subjects in our center [23][24][25]. Diagnosis of zinc deficiency in our laboratory is based on zinc levels in lymphocytes and granulocytes in SCD patients [12,20,[23][24][25].…”
Section: Studies In Patients With Sickle Cell Disease (Scd)mentioning
confidence: 99%
See 1 more Smart Citation